2012
DOI: 10.1016/s0924-9338(12)74309-2
|View full text |Cite
|
Sign up to set email alerts
|

P-142 - Heart rate variability spectral analysis in patients with panic disorder compared with healthy controls

Abstract: Power spectral analysis of electrocardiogram is known to be a particularly successful tool in detection of autonomic instabilities in various disorders. The aim of study is to measure very low frequency band (VLF), low frequency band (LF) and high frequency band (HF) components of R-R interval during orthostatic test in patients with panic disorder and a comparison with controls. Methods: We measured HRV in 31 panic disorder patients and 20 healthy controls. Patients were treated with psychotropics. Autonomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 0 publications
2
10
1
Order By: Relevance
“…The general conclusion is that during hypnosis, HRV increases without a concomitant change in heart rate, suggesting an increase in parasympathetic modulation of cardiac activity 16–18. The two HRV studies that assessed the tendency to dissociate show that a high tendency to dissociate is significantly related to decreased HRV 19 20. This finding corresponds with the results of investigations in patient populations with dissociative symptoms: patients with FNSS demonstrate lower HRV compared with healthy controls 21 22.…”
Section: Resultssupporting
confidence: 78%
“…The general conclusion is that during hypnosis, HRV increases without a concomitant change in heart rate, suggesting an increase in parasympathetic modulation of cardiac activity 16–18. The two HRV studies that assessed the tendency to dissociate show that a high tendency to dissociate is significantly related to decreased HRV 19 20. This finding corresponds with the results of investigations in patient populations with dissociative symptoms: patients with FNSS demonstrate lower HRV compared with healthy controls 21 22.…”
Section: Resultssupporting
confidence: 78%
“…and panic disorder (Diveky et al, 2012) show that they may have persistently reduced parasympathetic activity compared to healthy controls. These studies also found an inverse correlation between dissociative symptom scores and parameters of parasympathetic activity.…”
Section: Peripheral Physiologic Correlates Of Pathological/ Nonpathological Dissociationmentioning
confidence: 99%
“…Although patients do not have any full-blown cardiac disease, they have imbalanced autonomic regulation, reduced heart rate variability, increased time variability of ventricular repolarization, higher regional heterogeneity of ventricular repolarization and atrial depolarization 25 28 , and higher variability of ECG-R wave amplitude after beta-adrenergic stimulation with isoproterenol 29 . PD patients who are normotensive exhibit an impaired circadian blood pressure pattern with an inadequate reduction in nighttime blood pressure (non-dipper pattern) 30 as well as an unstable heart rate while asleep 31 .…”
Section: Are Panic Attacks Really the Results Of False Alarms?mentioning
confidence: 99%
“…At least in a certain proportion of patients with PD, PAs may be caused by paroxysmal supraventricular tachycardia 32 . In addition, these patients exhibit increased arterial stiffness, and several factors negatively affect endothelial function, such as increased homocysteine levels and platelet aggregation or volume and lower levels of nitric oxide 25 28 . Once more, these subtle abnormalities can render the cardiovascular system less efficient, and they are considered cardiovascular risk factors.…”
Section: Are Panic Attacks Really the Results Of False Alarms?mentioning
confidence: 99%